HUBUNGAN ANTARA PERFORMA PENGGUNAAN LEARNING MANAGEMENTS SYSTEM DENGAN PRESTASI BELAJAR SOSIOLOGI - Omika, Hefri Asra (Universitas Tanjungpura, 2022)
LMS has become a very important element in learning management. The activities of students in using the LMS are stored as log data. The data can be used as an indicator to measure the performance of students and show their achievements of students. This study aims to: (1) describe the level of learning achievement of students in sociology subjects based on Moodle LMS; and (2) know the relationship between student performance in using LMS and learning achievement in sociology subjects. This study is a correlational study with a research sample of 157. The sample selection was carried out using random sampling. Student performance data was obtained from Moodle log data which was measured using the number of activity ratings developed by Sigh et al. Learning achievement data is obtained from the average test scores for the odd semester and even semester for the 2021/2022 academic year. Data analysis used descriptive analysis and Pearson product-moment correlation analysis. The results showed that the level of learning achievement of class XII students was better than students of class XI and X. The test results showed that there was a significant relationship between the performance of using LMS and learning achievement in Sociology subjects.